A)
In order to find the x-intercepts you need to find the values of x which make:
[tex]y=0[/tex]
And in order to find the y-intercept you need to evaluate the function for:
[tex]x=0,y(0)[/tex]
So, for the equation:
[tex]\begin{gathered} 3x+12y=24 \\ \text{ Rewrite the equation as:} \\ y=2-\frac{1}{4}x \\ \text{The x-intercept is:} \\ y=0 \\ 2-\frac{1}{4}x=0 \\ 2=\frac{1}{4}x \\ x=8 \\ x-\text{intercept}=(8,0) \\ ----- \\ \text{The y-intercept is:} \\ y(0)=2-\frac{1}{4}(0)=2 \\ y-\text{intercept}=(0,2) \end{gathered}[/tex]
The mistake is replace y = 0 in order to find the x-intercept, you need to find the values of x which make the function equal to 0, not replace y for 0.
b.
[tex]\begin{gathered} y=2-\frac{1}{4}x \\ \text{ Remember find the values of x which make y = 0} \\ y=0 \\ 2-\frac{1}{4}x=0 \\ \text{solve for x:} \\ 2=\frac{1}{4}x \\ x=8 \end{gathered}[/tex]